ANALISA KANDUNGAN KIMIA PADA TEPUNG PISANG DENGAN METODE ANNEALING DAN RETROGRADASI PADA PEMBUATAN BISKUIT - Ruhil Fida (Program Studi Agribisnis Fakultas Pertanian Universitas Baturaja, 2022)
This study aims to determine the chemical content of biscuit products using modified banana flour by annealing and retrogradation. It consisted of three treatments, each treatment was repeated 6 times. The results showed that 10.01% of B treatment biscuits and 10.43% of C treatment biscuits met the SNI quality requirements. The highest ash content was found in C treatment biscuits modified double retrogradation banana flour and wheat flour (75:25) of 2 .53%. the fat content of biscuit products ranges from 16.44% – 18.68%. the carbohydrate content of each treatment was 60.92% - 65.31%.Keywords: annealing, double retrogradation, chemical content analysis.